2018
DOI: 10.3389/fpsyg.2018.01796
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year-Olds Solved a Mental Rotation Task Above Chance Level, but No Linear Relation Concerning Reaction Time and Angular Disparity Presented Itself

Abstract: Three-year-olds and 4-year-olds have severe difficulties solving standard mental rotation tasks. Only 5-year-olds solve such tasks above chance reliably. In contrast studies relying on simplified mental rotation tasks indicate that infants discriminate between an object and its mirror image. Furthermore in another simplified mental rotation task with 3-year-olds, a linear relation between angular disparity and reaction time typical for mental rotation was revealed. Therefore it was assumed that 3-year-olds’ ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 29 publications
(48 reference statements)
3
15
0
Order By: Relevance
“…Concretely, mental rotation improves at 6 compared to 5, and at 7 compared to 6. Although mental rotation abilities start to develop very early in infancy, showing the very first signs at 6 months (Frick, Möhring, & Newcombe, ), it seems that mental rotation abilities really start to improve at the age of 3 (Kruger, ) and performance becomes steadier at the age of 5 (Frick, Ferrara, & Newcombe, ), but we have also verified that this development still continues at the age of 7, although until 10 children do not reach the same accuracy as adults in this ability (Wimmer, Robinson, & Doherty, ). Accurate visuospatial functioning and memory in regular development have been associated with number‐related skills and spatial processing (Cornu, Schiltz, Martin, & Hornung, ; Crollen & Noel, ) that finally could affect some learning abilities, mainly arithmetic accuracy and mathematical achievement (Foley, Vasilyeva, & Laski, ; Li & Geary, , ).…”
Section: Discussionsupporting
confidence: 54%
“…Concretely, mental rotation improves at 6 compared to 5, and at 7 compared to 6. Although mental rotation abilities start to develop very early in infancy, showing the very first signs at 6 months (Frick, Möhring, & Newcombe, ), it seems that mental rotation abilities really start to improve at the age of 3 (Kruger, ) and performance becomes steadier at the age of 5 (Frick, Ferrara, & Newcombe, ), but we have also verified that this development still continues at the age of 7, although until 10 children do not reach the same accuracy as adults in this ability (Wimmer, Robinson, & Doherty, ). Accurate visuospatial functioning and memory in regular development have been associated with number‐related skills and spatial processing (Cornu, Schiltz, Martin, & Hornung, ; Crollen & Noel, ) that finally could affect some learning abilities, mainly arithmetic accuracy and mathematical achievement (Foley, Vasilyeva, & Laski, ; Li & Geary, , ).…”
Section: Discussionsupporting
confidence: 54%
“…Adult participants typically achieve near-perfect accuracy in this task, both with 3-dimensional forms rotated in depth, as in the original versions of the task, and also with 2-dimensional forms rotated in the picture plane (Cooper, 1975;Cooper & Shepard, 1973;Shepard & Cooper, 1982;Shepard & Metzler, 1971;Tarr & Pinker, 1989). Children are able to solve similar mental rotation tasks by the age of 5 years (Ehrlich, Levine, & Goldin-Meadow, 2006;Estes, 1998;Frick, Daum, Walser, & Mast, 2009;Frick, Ferrara, & Newcombe, 2013;Funk, Brugger, & Wilkening, 2005;Kosslyn, Margolis, Barrett, Goldknopf, & Daly, 1990;Marmor, 1975), and they can contrast rotated mirror images at even younger ages, when tested in more ecological conditions (Frick, Hansen, & Newcombe, 2013) or given appropriate training (Krüger, 2018;Marmor, 1977). For example, after two training sessions where they could actively rotate displays on a touch screen, 3year-olds proved able to associate novel pictures presented at various orientations with a sense match presented upright (Krüger, 2018).…”
Section: Sensementioning
confidence: 87%
“…Further discussion of MR in preschoolers is beyond the scope of this review, but it is notable that no consistent pattern of sex differences in young children's MR has been reported. For example, neither Krüger (2018) nor Krüger et al (2014) observed sex differences in their preschool-aged research participants. However, Levine et al (1999) reported a substantial advantage for male over female 4.5-year-olds on a spatial transformation task, which included both rotation and translation items, and Frick, Hansen, and Newcombe (2013) reported some sex differences as well with 3-year-old participants.…”
Section: Mental Rotation Of 3d Objectsmentioning
confidence: 93%
“…Other studies failed to find evidence for MR in children younger than 5 years old, and claimed that the failure to find MR in preschoolers reflects a true lack of ability, as opposed to difficulties with the test (e.g., inability to understand instructions; Frick, Ferrara, & Newcombe, 2013;Quaiser-Pohl, Rohe, & Amberger, 2010). Other studies, however, have demonstrated that even 3-and 4-year-olds provide evidence of MR in simplified tasks (Frick, Hansen, & Newcombe, 2013;Krüger, 2018;Krüger, Kaiser, Mahler, Bartels, & Krist, 2014;Levine, Huttenlocher, Taylor, & Langrock, 1999).…”
Section: Mental Rotation Of 3d Objectsmentioning
confidence: 99%
See 1 more Smart Citation